2022
DOI: 10.1136/bmjopen-2021-056878
|View full text |Cite|
|
Sign up to set email alerts
|

Acupuncture for low back and/or pelvic pain during pregnancy: a systematic review and meta-analysis of randomised controlled trials

Abstract: ObjectiveAcupuncture is emerging as a potential therapy for relieving pain, but the effectiveness of acupuncture for relieving low back and/or pelvic pain (LBPP) during the pregnancy remains controversial. This meta-analysis aims to investigate the effects of acupuncture on pain, functional status and quality of life for women with LBPP pain during the pregnancy.DesignSystematic review and meta-analysis.Data sourcesThe PubMed, EMBASE databases, Web of Science and Cochrane Library were searched for relevant ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 51 publications
1
6
0
2
Order By: Relevance
“…Yao et al 29 and Yang et al 20 showed that acupuncture was superior to the treatment provided to the control group. However, they focused on evaluating the efficacy of acupuncture and SC; SAcu was not involved and there was no appropriate blinding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yao et al 29 and Yang et al 20 showed that acupuncture was superior to the treatment provided to the control group. However, they focused on evaluating the efficacy of acupuncture and SC; SAcu was not involved and there was no appropriate blinding.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the effectiveness of acupuncture in the treatment of musculoskeletal pain, many physical therapists are unwilling to use it in pregnant women, as they believe that some points might trigger uterine contractions, inducing preterm labor, associated with the risk of litigation. 2 A recent systematic review 20 involving 10 studies with 1040 women with LBP and/or PGP during pregnancy showed that compared with standard care (SC), acupuncture was associated with pain relief, functional status, and quality of life (QOL) improvement. Moreover, no severe adverse effects were observed in the newborns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 and endometriosis-related pain. 21,22 A systematic review and meta-analysis of four randomized controlled trials in women with CPP concluded that the addition of acupuncture may benefit routine pain treatment, though the study quality was mostly interpreted as low. 23 Despite this, focused studies evaluating acupuncture intervention for patients with CPP are needed.…”
Section: Sleepmentioning
confidence: 99%
“…Bu sayede özel noktaların altından geçen enerji kanalları ile bu kanallar üzerinde bulunan organlar arasında ilişki kurulmaktadır. 2,3,6 Akupunktur, geleneksel Çin Tıbbı'nın Jing Luo (hatağ) teorisine dayalıdır. Bu teoriye göre insan vücudundaki organ ve dokular özel hat ve ağlar ile bağlanmakta ve yaşam enerjisi ile dolmaktadır.…”
unclassified